The Earth's Core - Crossley, David (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1993)
Summary The current status of knowledge of the Earth's inner and outer cores is reviewed from the stand points of seismology, gravity, Earth rotation, and the geomagnetic field. Because of the remoteness of the deep interior, geophysicist shave used great ingenuity in processing and interpreting surface data that is contaminated by many local (surficialand crustal) sources. Despite the lack of direct data from the deep Earth, there has been a rapid growth in knowledge inthe last decade due to advances in instrumentation and the blossoming of interdisciplinary studies. Of major interest at the present time is the interaction between the mantle and core, each of which contains a major convective regime, powering, in one case, plate tectonics and, in the other, the geodynamo. These regimes meet at the core-mantle boundary (CMB), which has provided a tempting target for seismology, magnetism, geodesy and high-pressure physics; much has been learned from the interchange between geophysicists in these disciplines. In this review, it is suggested that the pre-dominant themes for the next decade, growing naturally out of existing trends, are 1) improvements in the quality and coverage of global data sets, particularly those in geomagnetism, geodesy and seismology, 2) increased international co-operation through participation in interdisciplinary studies such as SEDI (Study of the Earth's Deep Interior), and 3) exploration of the non-linear aspects of dynamics within theEarth. Core studies are clearly not undertaken primarily for their social relevance, nor for any quick economic spin-off. The primary goal is to understand the structure, dynamics and evolution of the deep interior, as a prelude, it is to behoped, to the exploration of other planets. Each component of our national science effort is involved in this exciting and challenging goal. We need government institutions to provide the long-term economic stability with which to carry through essential observational campaigns at the surface, particularly as part of interdisciplinary, global initiatives. We need educational institutions to provide the leadership and vision with which to stimulate the science and train students. The university community benefits from the financial support of large companies to assist in the support of students and to sponsor specialized research projects, wherever the goals of industry and basic science connect. Last, and by no means least, we need the moral support of our population to allow the pursuit of these fundamental questions.